2004
DOI: 10.1039/b311176h
|View full text |Cite
|
Sign up to set email alerts
|

Dioxin-like compounds in pine needles around Tokyo Bay, Japan in 1999

Abstract: Pine needle samples collected at ten spatially distant sites around Tokyo Bay in 1999 indicated a widespread lower troposphere pollution with ultra-trace dioxin-like compounds such as chlorodibenzo-p-dioxins (PCDDs), -furans (PCDFs), non-ortho- and mono-ortho-chlorobiphenyls (pPCBs), and -naphthalenes (PCNs). Elevated concentration of planar PCBs and the total PCNs were found at the sites which are located innermost to the Bay, suggesting the regional importance of the evaporative nature of the source of pollu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 25 publications
3
22
1
1
Order By: Relevance
“…Korean pine needles contain the highest PCDD/F concentrations, 26.2−2088 pg/g dw 18 and 10.1−155 pg/g wet weight. 28 Chinese pine needles were found to have high levels relative to other developed countries such as Japan, 17 Germany, 12 and Poland. 29 Chen et al 19 reported that the PCDD/F concentrations in pine needles from Dalian were 87− 167 pg/g dw.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Korean pine needles contain the highest PCDD/F concentrations, 26.2−2088 pg/g dw 18 and 10.1−155 pg/g wet weight. 28 Chinese pine needles were found to have high levels relative to other developed countries such as Japan, 17 Germany, 12 and Poland. 29 Chen et al 19 reported that the PCDD/F concentrations in pine needles from Dalian were 87− 167 pg/g dw.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The composition of the raw materials used in thermal processes may affect the PCN emissions, and studies have shown that increasing the amount of recycled materials used leads to increased emissions of PCNs and dioxins from iron ore sintering processes (Xhrouet and De Pauw, 2004;Liu et al, 2012b). sources in industries that use thermal processes, or evaporative releases from historical uses of industrial chemicals (such as Halowaxes) (Jarnberg et al, 1997;Harner et al, 1998;Hanari et al, 2004;Schuhmacher et al, 2004;Gewurtz et al, 2009). The PCN concentrations and profiles in technical PCB and PCN formulations have been reported in detail Yamashita et al, 2000;Noma et al, 2004;Falandysz et al, 2006a,b;Falandysz, 2007;Falandysz et al, 2008).…”
Section: Concentrations and Teqs Of Pcn Emissions From Different Indumentioning
confidence: 99%
“…Isotope labeled ( 13 C 12 ) non and mono-ortho chlorobiphenyl congeners were used as internal standards (PCB mixture-EC-4937). Details of PCB determination (extraction, cleanup and fractionation, multi-layer silica gel cleanup step, alumina layer cleanup and fractionation step, hypercarb-HPLC fractionation of sub-step, and PYE-HPLC fractionation of sub-step) have been described previously (Hanari et al 2004).…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%